Effect of soil porosity and slope gradient on the stability of weathered granitic hillslope. - Muhammad Mukhlisin; Mohd Raihan Taha (Fakulti Kejuruteraan ,UKM,Bangi., 2011)
Modeling rainwater infiltration in slopes is vital to the analysis of rainfall induced slope failure. Amongst the soil hydraulic properties, the hydraulic conductivity K and considered as the dominant factor affecting the slope stability. Of less prominent was the effect of water retention characteristics. In this study, a numerical model was developed to estimate the extent of rainwater infiltration into an unsaturated slope, the formation of a saturated zone, and the change in slope stability.This model is then used to analyze the effects of the soil porosity parameters(i.e.,saturated soil water content q, and effective soil porosity (ESP) and slope gradient on the occurrence of slope failure. Results showed that when the surface soil of a slope has a relatively large ESP value, it has agreater capacity for holding rainwater, and therefore delays rainwater infiltration into the subsurface layer. Consequently, the increase in pore water pressure in the subsurface layer is also delayed. In this manner, a relatively large surface layer ESP value contributes to delaying slope failure. In addition,the slope gradient of slope is also a significant parameter in slope stability analysis. The time taken for gentle slope to reach failure is longer compared to similar cases with 40 slope gradient.